SYNTHESIS OF BIODIESEL FROM CLOVE OIL VIA TRANSESTERIFICATION - admin, Z. MUHAMMAD; I. MAINA; A. M. ALIYU; D. ABUBAKAR; S. MUHAMMAD; DALHATU, S.A.; U. I. ISMAIL, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The demand for biodiesel as a sustainable and renewable alternative fuel for diesel engines is steadily increasing due to economic and environmental reasons. Biodiesel can be obtained from vegetable oils (both edible and non- edibl e) and from animal fat. The synthesis of biodiesel via transesterification of clove biodiesel oil wa s investigated. Crude clove oil was subjected to purification, then transesterification using methanol and NaOH. FTIR characterization was employed to determine the functional group (presence of biodiesel) of crude, purified and transesterified Clove oil. The FT-IR shows that the ester was produced between 723.10354 cm−1 and 1740.66677 cm−1 peaks in the transesterified sample. This signifies the production of biodiesel.